Glycemic Index Values of Stiff Porridge (Ugali) Prepared from Maize, Millet, and Sorghum Flours: Which One for Diabetes Management? - Lorraine Amwoma; Rebecca Ebere; Joshua Arimi (Advances in Public Health)
Background. The prevalence of diabetes mellitus is increasing worldwide. Knowledge of glycemic index (GI) is important in its prevention and management. The GI measures how rapidly or slowly the blood glucose increases after food consumption. Stiff porridge (ugali) is an African cuisine that can be prepared from various cereal grains and consumed alongside a relish, including milk. The impact of cereal grain type and milk on the GI of ugali is not understood. Objectives. To determine the GI of ugali prepared from maize, millet, and sorghum and establish the impact of fermented milk on the GI. Methods. Proximate composition was determined using the Association of Official Analytical Chemists methods. Moisture, fat, protein, ash, and crude fiber content were determined by oven drying, soxhlet, Kjeldahl, dry ashing, and Hennenberg and Stohmann methods, respectively. Carbohydrate content was determined by difference. The GI was determined using standard procedures (ISO 26642:2010). Blood sugar response curves were generated using Microsoft Excel software. The GI was computed by dividing the incremental area under the curve (IAUC) of test food by the IAUC of glucose and then multiplied by 100. Data were analyzed using GenStat 14th Edition software. Results. Maize ugali had significantly higher carbohydrate content as opposed to millet or sorghum ugali (P<0.05). The GI for plain ugali followed the order sorghum (72) > maize (67) > millet (46). When consumed alongside fermented milk, the GI order was maize (70) > millet (67) > sorghum (57). Conclusion. Millet-based ugali may be used in the management of diabetes. Fermented milk lowers the GI of sorghum ugali and increases the GI of maize and millet ugali.